LITERATURE REVIEW: IMPLEMENTASI INTERVENSI DALAM MANAJEMEN KONFLIK KEPERAWATAN DI RUMAH SAKIT - Nathania, Nana; Widya Lestari; Amalia Yunita; Endang Dwi Rukmini; Etra Fianus Hendri; Issa Masri Anof; Luthi Pratiwi; Riza Fouzia Khainingsih; Triswan Simatupang (IKES Payung Negeri Pekanbaru, 2025)
Conflict is an unavoidable phenomenon in nursing practice due to multidisciplinary interactions, high workloads, and the demands of healthcare services. Poorly managed conflict can decrease nurses’ job satisfaction and service quality, whereas effective conflict management can strengthen communication and team collaboration. This study aims to examine various interventions used in nursing conflict management and evaluate their effectiveness through a literature review. Article searches were conducted in the Garuda, SINTA, PubMed, Wiley Online Library, and BioMed Central databases with inclusion criteria consisting of full-text research articles published between 2019 and 2025 and relevant to nursing conflict management. Of the 93 articles identified, six met all inclusion criteria. The findings indicate that conflict management interventions improve nurses’ interpersonal communication skills, self-efficacy, readiness to face conflict, job satisfaction, team collaboration, and perceptions of patient safety. De-escalation training and violence prevention strategies also reduced uncivil behavior, incidents of workplace violence, and the use of physical restraints. Overall, effective nursing conflict management requires a multilevel approach involving individual skill training, organizational support systems, and the application of nursing theory to create a collaborative, safe work environment focused on patient safety and enhanced nurse job satisfaction.